Fungsi dan Gaya Kepemimpinan Islam Berdasarkan Role Model Kyai Nusantara di Pondok Pesantren - Fivin Zuyyinatul Jannah; Qanita Rizqan Mazidah; Raditya Sandy Alfarizky; Fadhila Shifa; Ahmad Azzam Fi’lu Khoir; Mardiyah Mardiyah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to analyze the functions and styles of Islamic leadership based on the role models of Nusantara kyai in Islamic boarding schools. This study uses library research. Research data were obtained through observation, documentation, and observation of the leadership activities of kyai in the Islamic boarding school environment. Data analysis techniques were carried out through data reduction, data presentation, and descriptive conclusion drawing to obtain a comprehensive understanding of Islamic leadership practices in Islamic boarding schools. The results show that the leadership functions of kyai include educational, spiritual, social, and transformational functions in fostering students and the community. In addition, the leadership style of kyai tends to be charismatic, paternalistic, and participatory by placing exemplary behavior (uswah hasanah) as the core of leadership. The novelty of this study lies in the integration of the functions and styles of Islamic leadership within a leadership framework based on the role models of Nusantara kyai in Islamic boarding schools. This research contributes to the development of the concept of Islamic leadership that is contextual to the culture of Islamic boarding schools in the archipelago and provides practical implications for strengthening the model of Islamic educational leadership that is adaptive, moral, and relevant in facing the challenges of educational modernization in the contemporary era.Keyword: Islamic Leadership, Kyai Nusantara, Leadership Style, Leadership Function